2002
DOI: 10.1046/j.1365-2265.2002.01470.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of urinary phyto‐oestrogen excretion to BMD in postmenopausal women

Abstract: From these results, we conclude that urinary phyto-oestrogens, especially enterolactone and apigenin, are related to BMD in Korean postmenopausal women. Our results also suggest the possibility that phyto-oestrogens have differential effects on bone density. Further studies are needed to clarify the exact biological roles of phyto-oestrogenic components on bone metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 30 publications
(112 reference statements)
2
28
3
Order By: Relevance
“…Of the studies reported, Chinese and Dutch women excreted higher amounts of urinary lignans (den Tonkelaar et al, 2001) whereas Asian populations in China (Roach et al, 1998;Dai et al, 2002) and Japan (Uehar et al, 2000;Arai et al, 2000) excreted higher amounts of isoflavones. Interestingly, urinary isoflavone concentrations in Korean women were similar to those in Americans (Kim et al, 2002). We report nationally representative urinary concentrations of phytoestrogens in the US population.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Of the studies reported, Chinese and Dutch women excreted higher amounts of urinary lignans (den Tonkelaar et al, 2001) whereas Asian populations in China (Roach et al, 1998;Dai et al, 2002) and Japan (Uehar et al, 2000;Arai et al, 2000) excreted higher amounts of isoflavones. Interestingly, urinary isoflavone concentrations in Korean women were similar to those in Americans (Kim et al, 2002). We report nationally representative urinary concentrations of phytoestrogens in the US population.…”
Section: Introductionmentioning
confidence: 58%
“…Through this mechanism and others, phytoestrogens are thought to protect against coronary heart disease ( Clarkson and Anthony, 1998;Cassidy and Griffin, 1999). Additionally, phytoestrogen consumption has been linked loosely with relief of menopausal symptoms such as hot flashes, although the validity of these data are under debate (Adlercreutz et al, 1992;Vincent and Firzpatrick, 2000;Kim et al, 2002;Kurzer, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, bone density studies have investigated the correlation between endoc r i n e f u n c t i o n a n d b o n e m e t a b o l i s m i n w o m e n (Ongphiphadhanakul et al 2000;Kim et al 2002) and the correlation between physical exercise and bone metabolism (Akisaka et al 1997;Vincente-Rodriguesz et al 2008). However, these were group comparison studies, and very few reports have described the relationship between physical development and BMD in specific age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies suggest that phytoestrogens are somewhat effective in maintaining BMD in postmenopausal women (58)(59)(60)(61)(62)(63)(64)(65). Moreover, recent results from the Women's Health Initiative Study, showing an unexpected lack of cardioprotective effects of HRT (22), pushed the research for alternative and natural strategies for managing and preventing osteoporosis.…”
Section: A Pharmacological Model: Phytoestrogens and Bone Healthmentioning
confidence: 99%